Penerapan Teknik Relaksasi Benson Untuk Menurunkan Nyeri Pada Pasien Post Sectio Caesarea di RSUD dr. R Goeteng Taroenadibrata Purbalingga - Ismayani, Novita; Wibowo, Tophan Heri; Suryani, Roro Lintang (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: The number of SC deliveries in recent times has increased tremendously. This is a variable phenomenon related to social, economic and cultural levels SC has become a very safe procedure in many parts of the world so it is considered almost perfect. Procedures, operations may cause discomfort and alter tissue continuity. (Number, 2022). Objective: Based on this PkM, namely to determine the results of the application of benson therapy to reduce pain levels in post SC patients. Methods: The upcoming PKM method applies the benson relaxation technique as a nursing care approach to post SC surgery patients who experience pain. After being given benson relaxation therapy there was a decrease in the pain scale from 6 to scale 3. Community service activities are carried out by implementing directly by applying the Benson Relaxation technique. The target audience of this PkM is pregnant women who have undergone labor through the SC technique at RSUD dr. R Goeteng Taroenadibrata Purbalingga. Results: The results that have been carried out participants experienced an increase in pain before being given the application of benson relaxation techniques as many as 27 participants (90%) experienced moderate pain (4-7), after being given benson relaxation participants experienced a decrease in pain levels, namely 25 participants (83%) experienced a decrease to mild pain (<4). Outputs: The output of the activity used is a publication article that is expected to be able to hunt down Objective: This community service activity aims to help reduce post-SC pain with benson relaxation, patients can overcome it with non-pharmacological therapy independently. Method: This community service activity is carried out directly by providing the application of the benson relaxation technique, then continuing to evaluate so that the giver of the application of the benson relaxation technique can find out whether the target has decreased pain or not. The activity of applying the benson relaxation technique was carried out for 1 day for 10-15 minutes in the afternoon. The activity measures the patient's pain intensity using the VAS (Visual Analog Scale) measuring instrument. this activity is implemented directly to reduce pain in post SC patients at Dr. R Goeteng Taroenadibrata Purbalingga Hospital in the Bougenvile Room from July 15-28, 2024. Result: Participants experienced an increase in pain before being given the application of benson relaxation techniques as many as 27 participants (90%) experienced moderate pain (4-7), after being given benson relaxation participants experienced a decrease in pain levels, namely 25 participants (83%) experienced a decrease to mild pain (<4). Conclusion: Community Service participants in the application of benson relaxation techniques to reduce pain in SC patients in the Bougenvile Ward Room of RSUD dr. R Goeteng Taroenadibrata Purbalingga as a whole amounted to 30 participants, most in the age range 21-35 as many as 22 participants (73%), and the highest level of education is high school education as many as 14 participants (46.7%), with the most history of previous operations there has never been a history of previous operations as many as 21 participants (70%). Participants experienced increased pain before being given the application of benson relaxation techniques as many as 27 participants (90%) experienced moderate pain (4-7), after being given benson relaxation participants experienced a decrease in pain levels, namely 25 participants (83%) experienced a decrease to mild pain (<4).